Digital Terrestrial Television Broadcasting (DTTB) in Botswana: Prospects and Challenges - Mosanako, Seamogano; Lesitaokana, William O. (Television in Africa in the digital age, 2021)
The year 2015 was set by the International Telecommunication Union (ITU) for most of its member states globally to switch from analogue to digital terrestrial broadcasting. Digital television broadcasting is generally implied as transmission of broadcast content signals in the form of binary data, speciﬁcally 0 s and 1 s. Digitisation of television merges broadcasting, computing and telecommunications to transform both the way television content is made and consumers interact with content (Chalaby and Segell 1999). Referring to digital content, Flew (2004) suggested that digitisation of media and communication content grows “informatisation” of society.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Botswana (corpus analysé); Botswana (lieu de production du savoir); _Nettoyé

Analysing How Zimbabwe Broadcasting Corporation (ZBC TV) and Eswatini TV (ESTV) Are Adapting to the Digital Era - Lunga, Carolyne M.; Musvipwa, Rosemary (Television in Africa in the Digital Age, 2021)
The internet has impacted on how media organisations do journalism. Many media organisations both print and broadcast now have an online presence to reach out to fragmented audiences that have migrated to online platforms. Television stations have increasingly embraced the use of digital (online) media to gain better access to their audiences in terms of content distribution and audience engagement. The rise of social media platforms such as Facebook, Twitter, YouTube and Instagram have given journalists and media organisations the ability to reach their audiences immediately, with the added beneﬁt of audience responses which come almost immediately. The use of new digital media has created platforms for news stations to share digital clips of news items or excerpts of news programmes to keep the audiences informed or enticed by the highlights.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Eswatini (corpus analysé); Eswatini (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); Zimbabwe (corpus analysé); _Nettoyé

Digitization of Television in Kenya: Changing Trends in Content and Consumption - Murunga, Protus; Diang'a, Rachael (Television in Africa in the Digital Age, 2021)
The purpose of this chapter is to examine how the digitization of television has impacted the architecture of television content generation, dissemination consumption in Kenya. Its key motivation is to answer two main questions: How has the digitization shift in Kenya’s television impacted the trends in production, dissemination, reception and consumption of television content; what is the effect of digitization on viewer satisfaction; and how has this shift transformed the role of television medium in the country? The chapter, therefore, answers these questions focusing on the television channels under study, namely, Citizen TV, Kenya Broadcasting Corporation (KBC) and Nation TV (NTV).
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Kenya (corpus analysé); Kenya (lieu de production du savoir); _Nettoyé

Exodus, Access and Inequalities: The Impact of Digital Migration in the Least Developed Countries of Africa - Motsaathebe, Gilbert; Chiumbu, Sarah H. (Television in Africa in the Digital Age, 2021)
There has been a hype regarding the beneﬁts of digital migration, which refers to switchover from analogue to digital broadcasting. Commonly referred to as digital migration, the switchover emanates from a decision made at the International Telecommunications Union (ITU) in 2006 to release a valuable spectrum, which can be used for other services. Other beneﬁts of digital TV include good sound and picture quality and availability of more channels giving viewers more choice. It has also been said that digital broadcasting will save the broadcasting stations’ cost, as transmitting content via digital platforms is less costly than transmitting via the analogue platform (Muthomi 2012). This implies that media houses can capitalise on this migration as a competitive advantage. Countries across the world have been undergoing this necessary switchover from analogue to digital platforms, with varying degree of success. While the merits of digital television are clear, it is not clear how this digitisation will realistically help in bridging habitual inequalities in developing countries.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (lieu de production du savoir); _Nettoyé

Persuasion Across Platforms: A Rhetorical Analysis of Televised and Digitised News Reports on Economic Matters - Nkoala, Sisanda (Television in Africa in the Digital Age, 2021)
Audiovisual news media are compelling texts to study when it comes to how mass media shapes an audience’s perspective of the world (White 1998). This is due to the pivotal role these forms of media play in creating an informed citizenry as mediums that transmit information from news creators and news sources to the public as a mass audience (McQuail 1987). Even more signiﬁcant than this is the function of audiovisual news media as constructors of reality and ideology because of their pervasiveness in society (McLuhan and Fiore 1967; Hughes 1942). The advent of digital media has been touted as a means of diluting the inﬂuence of traditional mass media formats, such as television, with digital news media being forecast to take audiences away from these traditional media platforms (Lotz 2014).
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

Digital Disruption in South African Television News - Stos, Susan (Television in Africa in the Digital Age, 2021)
The term digital “disruption” conjures up negative connotations, with implications of disturbance, interference or interruption. Certainly, virtually every aspect of life has been affected by digitisation, but it has been pointed out that it is detrimental “only for those who chose to ignore it or try to ﬁght it” (“Digital Disruption: What Is It?” 2016, para 2). One case in point is the American company Kodak. Where it once dominated the ﬁlm and camera market for most of the twentieth century, the company recently ﬁled for bankruptcy. Kodak’s mistake was continually opposing the digitisation of the industry and failing to read the writing on the wall (“Digital Disruption: What Is It?” 2016). Digitisation is as much a reality of life in the newsroom as it is in the boardroom.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé